Optimalization of the Role of the School Principal as a Supervisor for Enhancing Teachers’ Pedagogical Competence: A Quantitative Study at State Elementary School 1 Pamotan Rembang Regency - Hikmah, Nurun; Haryati, Titik; Sumarno, Sumarno (FKIP - Universitas Riau, 2025)
Quality education in elementary schools is closely tied to teachers’ pedagogical competence, which strongly influences student learning outcomes. In Indonesia, the improvement of this competence is mandated by Law No. 14/2005 on Teachers and Lecturers. As instructional leaders, school principals hold a strategic role in fostering teacher development through effective academic supervision. This study aims to examine the principal’s role at state elementary school 1 Pamotan, Rembang Regency, in enhancing teachers’ pedagogical competence. A qualitative case study design was employed, with data collected through in-depth interviews, classroom observations, and document analysis. Thematic analysis was used to explore supervisory practices and their impact on teacher performance. The findings indicate that the principal applied a structured and collaborative supervision process, comprising planning, implementation, follow-up, and evaluation. However, limited integration of educational technology and innovative teaching strategies was observed, reducing the overall effectiveness in improving learning outcomes. The study concludes that systematic supervision, supported by technology integration, innovation, continuous professional development, and structured feedback, is essential for strengthening teachers’ pedagogical competence and improving instructional quality.